Good family function decrease internet addiction and increase academic performance in senior high school students - I Putu Belly Sutrisna; I Gusti Ayu Endah Ardjana; Supriyadi Supriyadi; Lely Setyawati (Indoscholar Publication and the Indonesian Psychiatric Association, 2020)
Background: A good The Internet gives excellent benefits for education. Uncontrolled internet use causes internet addiction may cause a poor outcome, such as academic failure. Family functions hypothetically correlate with internet addiction and academic performance in adolescents at school. The research aims to see the correlations among family function with internet addiction and academic performance in adolescents at senior high school.Method: Participants consisted of 305 adolescents from public senior high school students aged 14-18 years old. This research is using an analytical, cross-sectional method. The family function was assessed by the Family Assessment Device-Indonesian version (FAD-Ina). Internet addiction was assessed with Internet addiction Test Indonesian version (IAT-Ina). The student’s academic performance was obtained from the school report card at that time.Results: The result of this research shows that 76.4% of senior high school students have an internet addiction. The family function had a positive correlation and significant result with internet addiction (R=0.336, p <0.05). The family function had a negative correlation and significant result with academic performance (R=0.176, p <0.05). Internet addiction had a positive correlation and significant result with academic performance (R=0.128, p <0.05). Good family function in adolescents has four times decrease for internet addiction risk compared with bad family function (OR=4.290).Conclusion: This research shows that there was a 76.4% prevalence of internet addiction in adolescents at senior high school. A good family function can decrease internet addiction andincrease academic performance in the adolescent. Good family function decreased internet addiction risk four times.